BUSINESS GAME AS A COMPLEX INTERACTIVE TECHNOLOGY - Tojimov Qodir Qudrat o’g’li (Journal of new century innovations, 2022)
Abstract This paper presents a bibliometric study of the relationship between business games and creativity and points out gaps in the proposal of research topics. For this, we performed a detailed analysis of 64 articles obtained through a systematic review of the literature, gathered from the Scopus and Web of Science platforms in the areas of business and engineering, published between 1970 and 2016. The data was analyzed by descriptive statistical analysis with the support of the affinity matrix. The results identify: 1) the main research method in this theme is the case study with a qualitative approach; 2) the United States, Canada and China are the countries that publish the most; 3) there has been an increase in publications on this topic in recent years; 4) the main sector for application of studies on this theme is the educational one, followed by the business sector; and 5) considering both creativity and business games, exploratory studies are predominant. For future research it is recommended: 1) to analyze the influence of creativity principles in business games; 2) research what are the constituent elements of a business game; 3) investigate how a game can stimulate or mediate the creative process of its participants.